Replacement incomes and taxes: A distributional analysis for the EU-15 countries - Gerlinde Verbist (University of Essex, Institute for Social and Economic Research (ISER), 2005)
In this paper we analyse how income taxation interferes with the logic and aims of the social security system. We investigate the distributional effects of the tax treatment of social benefits, and more specifically of old age pensions and unemployment benefits. We present a brief overview of the different ways of levying taxes on replacement incomes. We measure the distributional effects of these different tax treatments by comparing gross and net replacement incomes over income deciles. By calculating Gini and Kakwani indices, we also estimate the inequality reduction and the progressivity characteristics of taxes on replacement incomes. Having summarised the link between taxes and replacement incomes, as well as their distributional effects, we then try to distinguish if there is a link between the tax treatment of replacement incomes and the type of welfare state.
Keywords: C81; D31; H23; H24; H55; 330; income redistribution; social benefits; income taxes; social insurance contributions; microsimulation; European Union